Beyond action-specific simulation: domain-general motor contributions to perception. Issue 4 (April 2015) - Press, Clare; Cook, Richard
Highlights Motor processes influence the visual perception of a wide range of events. These mechanisms likely operate equivalently across social and non-social domains. It is unclear whether action perception benefits from a special motor contribution.